2021
DOI: 10.3856/vol49-issue2-fulltext-2481
|View full text |Cite
|
Sign up to set email alerts
|

Sea surface temperature in continental and insular coastal Colombian waters: observations of the recent past and near-term numerical projections

Abstract: Sea surface temperature (SST) simulation for the 1970-2007 period and its projection up to 2035 was carried out with the Regional Ocean Modeling System (ROMS) for the Colombian Caribbean Sea (CCS) and the Colombian Pacific Basin (CPB). Spatial bias using the International Comprehensive Ocean-Atmosphere Data Sets (ICOADS) and Operational Sea Surface Temperature and Sea Ice Analysis (OSTIA) for 1982-2007 shows an adequate representation of surface characteristics in both marine study regions, especially on the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…The overall behavior of the current profile in the study area for the semester showed surface currents to the south-east (90-170 • ) with mean velocities of 0.5 m/s and a maximum of 0.8 m/s (Figures 7 and 12). When surface winds decrease from August to November due to the weakening of the CLLJ [22,38,[43][44][45], the Caribbean Counter Current (CCC) or the Panama-Colombia Counter current are affected, reducing its presence in the central coastal area (CCA) of the Colombian Caribbean [26]. When CCC turns back from the CCA to the north area of Colombian Caribbean, the Panama Colombia Counter Current (PCCC) [38] flows northmost near the Colombian coast carrying warm waters and forming a mixing zone when approaching the Magdalena River's mouth [25].…”
Section: Dynamics Of the Water Columnmentioning
confidence: 99%
“…The overall behavior of the current profile in the study area for the semester showed surface currents to the south-east (90-170 • ) with mean velocities of 0.5 m/s and a maximum of 0.8 m/s (Figures 7 and 12). When surface winds decrease from August to November due to the weakening of the CLLJ [22,38,[43][44][45], the Caribbean Counter Current (CCC) or the Panama-Colombia Counter current are affected, reducing its presence in the central coastal area (CCA) of the Colombian Caribbean [26]. When CCC turns back from the CCA to the north area of Colombian Caribbean, the Panama Colombia Counter Current (PCCC) [38] flows northmost near the Colombian coast carrying warm waters and forming a mixing zone when approaching the Magdalena River's mouth [25].…”
Section: Dynamics Of the Water Columnmentioning
confidence: 99%
“…Climate in the Panama Bight is driven by the meridional translation of the Intertropical Convergence Zone (ITCZ) throughout the year. From December to April, the ITCZ moves southward, reaching its southernmost position at ∼ 1 • N (Dimar, 2020; Poveda et al, 2006;Villegas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Climate in the Panama Bight is driven by the meridional translation of the Intertropical Convergence Zone (ITCZ) through the year. From December to April, the ITCZ moves southward reaching its southernmost position at ~1°N (Dimar, 2020; Poveda et al, 2006;Villegas et al, 2021). During this season, north trade winds from the Caribbean Sea cross the Panama Isthmus through orographic gaps, forming the Panama surface wind jet, that affects the Panama Bight ~400 km towards the 55 equator (Rueda Bayona et al, 2007).…”
mentioning
confidence: 99%